Laundry Business Opportunities Of Covid-19: An Analyses From Maqashid Al Syariah - Arwin Arwin Adam; Besse Faradiba (Universitas Islam Negeri Alauddin Makassar, 2021)
This study aimed to analyze the laundry business opportunities in the midst of the covid-19 pandemic in Parepare. This study used feasibility analysis in some aspects including marketing, human resource management, technical and technological aspects, legal aspects and investment feasibility aspects in the form of Payback period (PP), Benefit Cost Ratio (BCR), Net Present Value (NPV) and Internal Rate of Return (IRR). The sampling technique was purposive sampling utilizing Firman Laundry and BMR Laundry as samples with data analysis of maqashid al sharia al Khassah ibn Asyur. The results of the research showed that the marketing aspect was feasible because it was strategically located. The human resource management aspect exhibited a simple organizational structure but was able to provide benefits. The technical and technological aspects had used a drying machine, a washing machine with steam technology, and the investment feasibility aspect obtained were from PP, BCR, NPV, IRR which both were able to exceed the profit target set by the business owner so that this business had a great opportunity despite the pandemic in Parepare. Besides, it produced a description maqashid Khassah by Ibn Asyur covering al rawaj, al wuduh, al-hifz, al tsibat and al adl.